Inside Cover: Me3Si−SiMe2[oCON(iPr)2−C6H4]: An Unsymmetrical Disilane Reagent for Regio‐ and Stereoselective Bis‐Silylation of Alkynes (Angew. Chem. Int. Ed. 17/2018). Issue 17 (13th March 2018) - Xiao, Peihong; Cao, Yanjun; Gui, Yingying; Gao, Lu; Song, Zhenlei
Abstract : Carried on butterfly wings The unsymmetrical air‐stable disilane, Me3 Si−SiMe2 [ o CON( i Pr)2 C6 H4 ], bis‐silylates terminal alkynes to yield Z ‐vinyl disilanes with high regioselectivity and good functional group tolerance. In their Communication on page 4769 ff., Z. L. Song et al. describe a transformation that is difficult to achieve using traditional halide or methoxy‐substituted unsymmetrical disilanes; a metamorphosis of cocoon‐like alkynes into butterfly‐like Z ‐vinyl silanes.